Case report – Selective internal radiation therapy (SIRT) in a patient with hyperinsulinemic hypoglycemia due to a metastatic insulinoma with late onset of endocrine activity - Henker, Robert; Lincke, Thomas; Hoffmeister, Albrecht (Zeitschrift für Gastroenterologie, 2022)
Insulinomas are the most common functioning pancreatic neuroendocrine tumors (NET), which can lead to hyperinsulinemic hypoglycemia. In advanced metastatic stages of the disease, the prognosis is poor. Patients with hormonally active insulinomas primarily present with features of neuroglycopenia. Transformation from a nonfunctional to a functional NET is rare. Here, we present a case of a 59-year-old male adult with a metastatic insulinoma and late onset of endocrine activity. Besides medical treatment with Diazoxide and small frequent feedings, continuous intravenous glucose application was eventually required to avoid hypoglycemia. Furthermore, we show that selective internal radiation therapy (SIRT) can be an effective therapeutic approach for symptom reduction in advanced metastatic disease.
Keywords: Darm; Gastro-entero-pankreatische Tumoren; Insulinom; SIRT; pNET; Hyperinsulinämie; Hypoglykämie